The dual immunomodulatory role of B cells in tumorigenesis: mechanisms, microenvironment crosstalk, and therapeutic implications - Lv, Zhuangwei; Yang, Ruohao; Zhang, Kai; Wang, Ruihan; Shi, Xiaoyu; Wu, Jinhua; Liu, LuLu; Jiao, Junna (Frontiers in Immunology, 2025)
B lymphocytes exhibit a multifaceted and context-dependent role in tumor biology, acting as both promoters and suppressors of malignancy through dynamic interactions within the tumor microenvironment (TME). This review synthesizes current evidence on the dual functions of B cells in tumor immunity, highlighting their capacity to orchestrate antitumor responses via antigen presentation, antibody-dependent cytotoxicity, and tertiary lymphoid structure (TLS)-mediated T cell activation, while paradoxically driving immunosuppression through regulatory B cells (Bregs), pro-angiogenic signaling, and immune checkpoint modulation. Key mechanisms include TLS formation, which enhances cytotoxic T cell priming and correlates with improved immunotherapy outcomes, and Breg-mediated secretion of IL-10/TGF-β, which fosters T cell exhaustion and myeloid-derived suppressor cell recruitment. Tumor-type specificity is evident: TLS-rich malignancies like melanoma and Non-Small Cell Lung Cancer (NSCLC) show B cell-driven immune activation, whereas pancreatic and hepatocellular carcinomas demonstrate B cell functional plasticity influenced by metabolic and epigenetic reprogramming. Therapeutically, B cell-targeted strategies—including CD20 antibodies, CAR-T cells, and B cell epitope vaccines—demonstrate efficacy in hematologic and solid tumors, yet face challenges due to subset heterogeneity and sex-specific response disparities. Emerging approaches combine immune checkpoint inhibitors (ICBs) with TLS-inducing agents or exploit B cell-derived biomarkers for personalized therapy. Future directions emphasize deciphering B cell metabolic-niche crosstalk, optimizing combinatorial regimens, and leveraging spatial multiomics to resolve functional heterogeneity. By bridging mechanistic insights with clinical translation, this work underscores B cells as pivotal regulators of tumor immunity and advocates for precision strategies to harness their antitumor potential while mitigating pro-tumor plasticity.